Pro-inflammatory biomarkers in women with non-obstructive angina pectoris and coronary microvascular dysfunction - Jakob Schroder; Naja Dam Mygind; Daria Frestad; Marie Michelsen; Hannah Elena Suhrs; Kira Bang Bove; Ida Gustafsson; Jens Kastrup; Eva Prescott (International Journal of Cardiology: Heart & Vasculature, 2019)
Background: Studies that evaluate larger numbers of protein biomarkers in patients with coronary microvascular dysfunction (CMD) have not previously been performed, and very little is known concerning the pathogenetic mechanisms leading to CMD.Our objective was to analyze associations between a broad cardiovascular disease (CVD) protein biomarker assay and CMD, and further explore internal biomarker relations in order to identify possible targets for future treatment interventions. Methods: In 174 women with angina pectoris and no significant obstructive coronary artery disease (<50% stenosis on invasive coronary angiography), CMD was assessed by transthoracic Doppler echocardiography measuring coronary flow velocity reserve (CFVR). Blood samples were analyzed with a CVD proteomic panel encompassing 92 biomarkers. The relation between biomarkers and CFVR was evaluated by regression analysis, and possible interrelations between significant biomarkers were investigated by principal component analysis (PCA). Results: Median age (SD) was 64 years (9.8), median CFVR (IQR) was 2.3 (1.9–2.7), and 28% of patients had CFVR < 2.0. Eighteen biomarkers were significantly correlated with CFVR. In PCA, 8 of the biomarkers significantly related to CFVR showed high loadings on principal component 1 (PC1). The component scores of PC1 were significantly related to CFVR (p = 0.002). The majority of the 8 interrelated PC1 biomarkers were related to the pro-inflammatory TNF-α – IL-6 – CRP pathway. Conclusion: Eighteen protein biomarkers were significantly associated with CMD. Eight biomarkers were interrelated in PCA, and share connection with pro-inflammatory pathways, highlighting a possible important role of inflammation in CMD. Keywords: Coronary microvascular dysfunction, Biomarkers, Principal component analysis